An assessment of the effectiveness of library resources and services in supporting researchers' information needs - Ayob, Arinawati (2011)
As one of the supporting departments of a university, the academic library plays an important role in providing essential information resources and services to the researchers. Changes in information technology have impacted libraries due to changes in the format of information resources and the information seeking behavior of users. Technology has transformed the way researchers seek, obtain and use information. Libraries therefore need to critically examine the effectiveness of their services in fulfilling their researchers‟ information needs. An assessment of the effectiveness of library services has been conducted at an academic library based on selected criteria in four domains stated in the literature; 1) resources 2) services 3) library/stakeholders interactions and 4) access. The result from the survey has provided ideas about the strengths and the weaknesses of the library services from the perspective of researchers.